Impact of microporous γ-Al2O3 on the thermal stability of pre-cast cementitious composite containing glass waste. (16th May 2023) - Mohamed, O.A.; Hazem, M.M.; Mohsen, Alaa; Ramadan, M.
Graphical abstract: Highlights: Using sodium-rich glass waste (SGW) as a supplementary cementitious material. Preparation and full characterization of microporous γ-Al2 O3 (MP-NA) Mechanical and textural characteristics for OPC + SGW + MP-NA composite. Hydrothermal curing effect on the properties of OPC + SGW + MP-NA composite. γ-Al2 O3 impact on the fire resistivity of OPC + SGW composite. Abstract: Upcycling sodium-rich glass waste (SGW) in fabricating pre-cast binding materials is the main motivation of this work. The impact of different curing regimes on the mechanical resistance of OPC-SGW pastes was investigated: normal curing under tap water as well as hydrothermal treatment at different pressures (3, 6, 9 and 12 bars). Replacing OPC with 50 wt% SGW (Blend-G composite) reduced the compressive strength by 30.9% under normal curing after 28 days, but the strength value was completely close to the OPC reading (68 MPa) under hydrothermal curing at 9 bars for 4 hrs. According to the fire resistance results, the compressive strength value of autoclaved Blend-G paste was reduced by 87 and 97.4% after firing at 500 and 750 °C, respectively. Therefore, it was necessary to search for a radical solution to solve this problem, and consequently, 1 wt% micro-porous gamma alumina nanoparticle (MP-NA) was incorporated into Blend-G to produce Blend-M composite. The MP-NA was prepared by the sol–gel method from low-cost commercial materials. Inclusion of 1 wt% MP-NA (Blend-M) enhanced the strength by 140, 48.4 and 31.9% after 1, 7 and 28 days, respectively and by 22.9% at 9 bars/4hrs than Blend-G. This may be attributed to the super-fine/nucleation effect, pore structure rearrangement, and high pozzolancity of MP-NA that increased the amount of binding hydrates (CSHs, CASHs, and CAHs), which was detected via XRD, TGA/DSC, and SEM. Moreover, high thermal stability up to 750 °C was observed for Blend-M due to the generation of new ceramic phases such as nepheline and Mullite.